Utilization of Snapper Spinach Leaf Extract (Amaranthus Hybidrus L) in Peel-Off Gel Mask Preparation for Aging Face Skin Care - Kartika, Ayu; Minerva, Prima (International Journal of Natural Science and Engineering, 2023)
The peel-off gel mask is a type of mask that is easy and practical to use. Besides that, it can also hydrate the skin well. Spinach contains chemicals that are good for skin health including vitamin A, vitamin E, vitamin C, and flavonoids. The purpose is to determine the feasibility of peel-off gel masks with snapper spinach leaf extract in terms of laboratory tests (vitamin A, vitamin C, flavonoids, homogeneity, pH, drying time), organoleptic tests (color, aroma, stickiness, and texture), and hedonic test (favourability level). This type of research is an experiment with quantitative analysis. The independent variable is snapper spinach leaves. The dependent variable is the content of vitamin A, vitamin C, flavonoids, homogeneity, pH, and drying time contained in the peel-off gel mask. Data analysis techniques are observation and documentation. The formulations used are X1 (1%), X2 (3%), and X3 (5%). The results showed that in the peel-off gel mask of spinach leaf extract, there was 9568,0000 ppm (9.57%) of vitamin A, 0.088% vitamin C, (+) flavonoids, the X1 and X2 formulations were homogeneous, while the X3 formulation not homogeneous, pH 4.86, and average drying time of 20 minutes. The best formulation in terms of organoleptic and hedonic tests is X2 (3%) quite colorful (55.56%), quite flavourful (66.67%), sticky (66.67%), smooth (100%), likes (66,67%). Thus, the peel-off gel mask with snapper spinach leaf extract is suitable as an aging skin treatment.